Peculiarities of brain structural changes in young patients with arterial hypertension - Mishchenko T. S.; Bokatueva Victoria; Mishchenko V. M.; Kharina K. V. (Psychiatry, Neurology and Medical Psychology, 2022)
Actuality: Arterial hypertension (AH) is one of the most common diseases among diseases of the circulatory system and, together with other cardiovascular diseases, ranks first in the world and in Ukraine in terms of mortality rates. About 45% of patients do not know that they have hypertension. The scale of this problem in the world is evidenced by the fact that hypertension is found in every third adult. This disease occurs more often in the elderly, but its development often begins at a young age, and sometimes even in childhood. The intensive development of neuroimaging methods (CT and MRI) in recent decades makes it possible to detect various changes in the brain at early preclinical stages, which is of great importance for the implementation of adequate differentiated primary prevention of the development and progression of cerebrovascular disease and such unpleasant manifestations as cognitive deficits, dementia and ischemic stroke. The purpose of the study: to reveal the nature of structural changes in the brain in young patients with clinically confirmed hypertension. Material and methods: a study of structural changes in the brain was conducted based on the MRI examination data (1.5 T) of 54 young patients (18-44 years old) with hypertension of various degrees. Statistical analysis was carried out by the IBM SPSS Statistics 20 license program using the criterion of agreement with the test of static significance (Fisher’s exact test -F). Results: Differences in brain structural changes were obtained in patients depending on the degree of hypertension. A significant difference according to the χ² criterion (р<0.05) was found in the frequency of occurrence of mixed, external and internal hydrocephalus in patients with hypertension of the first and second century. Differences in the incidence of external and internal hydrocephalus in patients with AH I and AH III, AH II and AH III not detected by the χ² criterion (p< 0.05). There are differences in the frequency of leukoaraiosis of the 0th, 1st, 2nd, and 3rd stages. according to the Fazekas scale between groups of patients with 1st stage hypertension, 2nd stage hypertension, and 3rd stage hypertension reliable according to the χ² criterion (р< 0.05). Differences in the frequency of lacunar foci at different degrees of hypertension were not reliably detected. The analysis of the results of the assessment of structural changes of the brain by age showed that the main differences in the occurrence of mixed and external hydrocephalus are characteristic of all age groups. There is no difference in the frequency of internal hydrocephalus, mild and moderate leukoaraiosis in the groups of men and women. The frequency of occurrence of mixed, external hydrocephalus, the absence of leukoaraiosis and the presence of severe draining leukoaraiosis (in men, the severity of these changes prevails) is significantly different. No difference in the frequency of lacunar foci was found in the groups of men and women. Conclusions: Thus, hypertension is an age-dependent disease. No differences were found in the frequency of complaints of noise in the head, decreased attention and cognitive activity, sleep disturbances, and gender differences in the examined patients with hypertension of various degrees of severity. The main structural changes of the brain in the examined patients are various types of hydrocephalic manifestations, signs of leukoaraiosis (characteristic for the older age of 36-44 years) of one degree or another. Some gender specific features of brain structural changes in the examined patients were revealed (increased manifestations of hydrocephalus syndrome in men and absence of leukoaraiosis in them compared to women).